2021
DOI: 10.3389/fimmu.2020.618231
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the NLRP3 Inflammasome by Post-Translational Modifications and Small Molecules

Abstract: Inflammation is a host protection mechanism that eliminates invasive pathogens from the body. However, chronic inflammation, which occurs repeatedly and continuously over a long period, can directly damage tissues and cause various inflammatory and autoimmune diseases. Pattern recognition receptors (PRRs) respond to exogenous infectious agents called pathogen-associated molecular patterns and endogenous danger signals called danger-associated molecular patterns. Among PRRs, recent advancements in studies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 131 publications
(177 reference statements)
2
49
0
2
Order By: Relevance
“…All these studies indicated that the translocation of the NF-κB p65 subunit is crucial for activating inflammation in DKD. On the other hand, the release of IL-1β is controlled by NLRP3 inflammasome activation [22,23,53]. NLRP3 activation may be involved in multiple inflammatory or stress pathways, including NF-κB signaling pathways [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All these studies indicated that the translocation of the NF-κB p65 subunit is crucial for activating inflammation in DKD. On the other hand, the release of IL-1β is controlled by NLRP3 inflammasome activation [22,23,53]. NLRP3 activation may be involved in multiple inflammatory or stress pathways, including NF-κB signaling pathways [23].…”
Section: Discussionmentioning
confidence: 99%
“…activation [22,23,53]. NLRP3 activation may be involved in multiple inflammatory or stress pathways, including NF-κB signaling pathways [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptidoglycan undergoes structural rearrangements in the process of bacterial growth and division. These autolytic functions are performed by intracellular peptidoglycan hydrolases and amidases, which destroy peptidoglycan and form muramyl peptides (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…However, altered Ca 2+ homeostasis and other ion fluxes (e.g., Na + and Cl − ) have also been implicated in NLRP3 activation [ 15 , 16 ]. Several studies demonstrated that reactive oxygen species (ROS) production, lysosomal destabilization and post-translational modifications are other cellular triggers able to promote the activation and assembly of NLRP3 inflammasome [ 17 , 18 , 19 , 20 , 21 ]. Once activated, NLRP3 undergoes a conformational change and then oligomerizes to give rise to a functional inflammasome, which can trigger the auto-proteolytic cleavage of pro-caspase-1 into the active caspase-1 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%